Differences in Effectiveness of Antibacterial Power Between Cocoa Peel Extract (Theobroma cocoa L.) and Benzalkonium Chloride 0.1% Against Staphylococcus aureus (In Vitro) - Yuanita, Tamara; Ceson, Mohammed Alaqsha Brysoul; Subiyanto, Agus (Conservative Dentistry Journal, 2021)
Background: Staphylococcus aureus is a gram-positive bacteria play a role in the formation of dental biofilm which is causing dental caries. During tooth preparation, to stop the growth of bacteria, a cavity cleaning agent is given using a chemical, namely Benzalkonium Chloride (BAC) 0.1%, but BAC has disadvantages including allergic reactions, tolerant microbes, and resistance. Therefore, it is hoped that there will be herbal ingredients that can be used as an alternative. Cocoa peel extract has active compounds of tannins, flavonoids, alkaloids, terpenoids, and saponins which have antibacterial concentration 6% according to safe concentrations. Purpose: To explain the difference in the effectiveness of the antibacterial power of 6% cocoa peel extract and 0.1% BAC against Staphylococcus aureus (in vitro). Methods: This study was a laboratory experimental in vitro with the posttest only control group design. Using the diffusion method for Staphylococcus aureus that divided into two parts, 6% cocoa peel extract and 0.1% BAC. Each petri dish was given disc paper dripped with 0.01 ml of each test material, then incubated for two days and observed the diameter of the inhibition zone. Results: The average diameter of the inhibition zone formed in the 6% cacao peel extract was 11.5288 mm and BAC 0.1% was 18.2925 mm against Staphylococcus aureus. Conclusion: There was a significant difference in the effectiveness of antibacterial power (p <0.05) between 6% cacao peel extract (Theobroma cacao L.) and 0.1% BAC against Staphylococcus aureus (In Vitro).